USING AUTHENTIC MATERIALS IN IMPROVING EFL STUDENTS’ ENGLISH SKILLS - Devie Reztia Anjarani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2017)
Nowadays, authentic materials are considered as important tools for the teachers in improving their EFL students language skills and moreover as an effective way in transmitting the knowledge to the students. In this paper, the writer will discuss more about how the authentic materials use can improve students’ four language skills since there are number of studies proved that authentic materials is useful in motivating and improving their language skills. Furthermore, this paper also will show the effectiveness of authentic materials applied on listening, speaking, reading, and writing classes.